WHO Global Initiative for childhood cancer - India responds (Elsevier, 2020)
Launched in 2018, the WHO Global Initiative on Childhood Cancer aims to reach at least 60% survival rate for children with cancers by 2030, while reducing suffering, altogether saving an additional one million lives. There is an opportunity for India to align with this Global Initiative and make progress. Over the last year several meetings at diverse platforms in India and abroad have engaged multiple stakeholders. This has led to an increased awareness of the Global Initiative, an agreement within the Indian community to be part of it, identification of key players, and initial discussions on the areas of focus and relevant organisations. In the next year, we aim to chalk out the details of the scope of the work, the structure of the activities, the timelines, the interim and final endpoints and the resources needed.